Extensão universitária na formação discente: experiências vividas na Casa Familiar Rural de Santarém - Pará - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
This TCC aims to discuss the contributions of university extension to the formation of students, and the challenges of its implementation within the scope of the extension project. It has been observed that compliance with the work plan requires academic flexibility, since reconciling full-time university activities with the way the project works is a challenge for the extension worker. In this sense, the evolution of the formation of the target audience and academia is offered.
Keywords: CFR; Educação; desenvolvimento acadêmico; interação universidade-campo; CNPQ:: CIÊNCIAS AGRÁRIAS